Influence of Additivation of Bio-Based Lubricants on Sprayability and Solubility for Cryogenic Minimum Quantity Lubrication - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
The development of innovative cooling lubrication strategies is significantly driven by the need to machine materials resistant to high temperatures while taking into account both ecological and economic aspects. Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in the manufacturing process. A minimal amount of oil is added to the cryogenic medium carbon dioxide (CO2) to ensure both cooling and lubrication during tool engagement. In this context, vegetable oils, so-called triglycerides, can be used with respect to the cooling lubrication concept. The aim of this paper is to analyze various bio-based oils with regard to their solubility, spraying and flow behavior and to investigate the influence of additives on the performance. During the lubrication tests, the additives have shown no influence on the lubricating effects. Thus the chemical properties of the base oils primarily influence the properties with regard to solubility and spray behavior. Finally, the collected results were correlated with machining tests showing only a limited correlation with the aforementioned lubrication tests.
Keywords: CMQL; Milling; Liquid carbon dioxide; Bio-based lubricants